2003
DOI: 10.1152/japplphysiol.00182.2003
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-mediated modulation of macrophage function after trauma-hemorrhage: central role of 5α-dihydrotestosterone

Abstract: Androgens have been implicated as the causative factor for the postinjury immune dysfunction in males; however, it remains unknown whether androgens directly affect macrophages. To study this, male mice were sham operated or subjected to trauma (i.e., midline laparotomy) and hemorrhagic shock (mean arterial pressure, 30 ± 5 mmHg for 90 min and then resuscitated). The mice received the 5α-reductase inhibitor 4-hydroxyandrostenedione (4-OHA) before resuscitation. Plasma TNF-α, IL-6, and IL-10 levels were elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…In agreement with the previous studies showing androgen suppression of innate immune response, our data show that phagocytic function in the spotless starling is strongly inhibited under moderate physiological concentrations of T (Slater & Schreck 1997; Al Afaleq & Homeida 1998; Schneider et al. 2003).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the previous studies showing androgen suppression of innate immune response, our data show that phagocytic function in the spotless starling is strongly inhibited under moderate physiological concentrations of T (Slater & Schreck 1997; Al Afaleq & Homeida 1998; Schneider et al. 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Whereas both testosterone and DHT provoked a significant increase in macrophage IL-6 gene expression without greatly affecting TNF-␣ or TGF-␤1 mRNA levels, fibroblast IL-6 and TGF-␤1 mRNA levels and protein secretion were significantly reduced by treatment with testosterone or DHT and TNF-␣ mRNA expression decreased in response to exposure to DHT. These findings are partially corroborated by previous studies which demonstrated that DHT and testosterone inhibit IL-6 production by oral and gingival fibroblasts and that DHT but not testosterone stimulates secretion of IL-6 by Kupffer cells (Coletta et al, 2002;Gornstein et al, 1999;Parkar et al, 1998;Schneider et al, 2003). The failure of testosterone to enhance macrophage TNF-␣ gene expression contrasts sharply with the situation in mice, in which testosterone has been shown to increase both basal and LPS-induced mRNA levels (Ashcroft and Mills, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…Other investigators have found divergent cytokine release when myocardia were exposed to estrogen and testosterone (1,2,10,40,49,51). Previously, we found that endogenous testosterone exposure increased myocardial cytokine production and decreased postischemic cardiac function, suggesting that endogenous testosterone exerts a deleterious effect on myocardium via increased myocardial inflamma- tion (45).…”
Section: Discussionmentioning
confidence: 62%